Cremanthodium botryocephalum and C. spathulifolium are both merged with Ligularia lagotis (Asteraceae, Senecioneae) - Wang, Long; Luo, Hong-Yi; Ren, Chen; Yang, Qin-Er (Phytotaxa, 2016)
Our examination of herbarium specimens and observations on living plants demonstrated that Cremanthodium botryocephalum and C. spathulifolium are both conspecific with Ligularia lagotis (Asteraceae, Senecioneae), and thus are synonymized herein.